Концепції організації галузевих ринків у зрізі інформаційно-комунікаційних послуг - Степаненко, С. В.; Цира, О. В.; Лагодієнко, В. В. (Підприємництво та інновації, 2023)
Радикальне перетворення науки та отримання на її основі інноваційних технологій з пропонованими сучасними послугами надає не лише новітні знання, але й підвищують її ефективність та вклад у економічний потенціал державного та світового рівнів. В якості новітнього напрямку виступають інформаційно-комунікаційні технології (ІКТ), які утворюють окрему ланку ринкових відносин, що сьогодні формує величезний економічний фундамент для розвитку суспільства в цілому. ІКТ надають людям можливість отримувати доступ до інформації та знань практично миттєво. Кожна людина має мати навички, необхідні для користування повною мірою перевагами інформаційного суспільства. Все це формує низку невирішених питань: обґрунтування теоретичних та методологічних засад до створення ринків сфери інформаційно-комунікаційних технологій, питань ефективного державного управління та формування відповідних інститутів влади, проблемних питань сучасних економічних відносин тощо. Radical transformation of science and obtaining on its basis innovative technologies with offered modern services not only provide the latest knowledge, but also increase its efficiency and contribution to the economic potential of the state and world levels. The newest trend is information and communication technologies (ICT), which form a separate link of market relations, which today forms a huge economic foundation for the development of society. The development and widespread use of modern information and communication technologies in all spheres of life in society is today a necessary condition for development and raising the standard of living of the population. Modern ICTs save time, increase the efficiency of the use of national and global information resources, contribute to increasing the general level of education of society and the development of its intellectual potential. ICTs enable people to access information and knowledge almost instantly. Each person must have the skills necessary to use it to the full extent of the benefits of the information society. All this forms a few unresolved issues: substantiation of theoretical and methodological foundations for the creation of markets in the field of information and communication technologies, issues of effective state management and the formation of relevant institutions of power, problematic issues of modern economic relations, etc. It is proven that sustainable economic growth will remain below the potential if the economy is not able to use new information and communication technologies and receive their benefits. It has been established that consideration of the ICT market should be divided into several components that interact with each other and influence each other. It is suggested that for an economic assessment of the situation in the ICT services market, one should turn to the calculation of the basic concentration ratio, which is an indicator that allows to study the general structure of the market. In the future, understanding the internal nature of development and the combination of information and communication technologies will allow not only to reveal the evolutionary nature of industries and the market, but also to understand the nature of their interaction with society and social institutions as forms of reflection of economic relations. Innovative solutions and technologies are a key link in the economic system of society. The presentation of the theoretical foundations is considered from the point of view of the interconnected logic of economic analysis at the levels: firm, sphere of application, society.
Concepts of the organization of industry markets in the section of information and communication services
Keywords: інформаційно-комунікаційні технології; послуги; ринок; ринкові відносини; інформаційне суспільство; information and communication technologies; services; market; market relations; information society